GAMBARAN TINGKAT KONSUMSI NATRIUM DAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI PUSKESMAS TABANAN III - Ardine Madyasari; Lely Cintari; Komang Wiardani (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Hypertension or better known as high blood pressure is a chronic disease due to excessive and insistent blood pressure on the arteries. Associated with hypertension and at risk of overcoming health problems After conducting several assessments, blood pressure values that indicate high blood pressure 140 mmHg and diastolic 90 mmHg. Hypertension continues to increase every year. Natrium consumption tightly increases blood pressure in hypertensive patients because consuming excess natrium causes thirst and encourages drinking, this increases the volume of blood in the body which means the heart has to pump more actively increasing blood pressure. This study discusses the level of natrium consumption and blood pressure in hypertensive patients at the Tabanan III Health Center. This type of research is observational research with cross sectional design and consecutive sampling techniques. The number of samples issued is 20 samples. From the research that has been done, from 20 samples have good natrium consumption level, samples with good natrium consumption category with uncontrolled blood pressure are 11 samples (100%) and good natrium consumption level with controlled blood pressure are 9 samples (100%).Keywords: blood pressure, natrium consumption, hypertension